2003
DOI: 10.1086/376558
|View full text |Cite
|
Sign up to set email alerts
|

High Rates ofTrichomonas vaginalisamong Men Attending a Sexually Transmitted Diseases Clinic: Implications for Screening and Urethritis Management

Abstract: Trichomonas is a cause of nongonococcal urethritis (NGU); however, studies of its prevalence in men have been hampered by the lack of sensitive diagnostics. DNA amplification allows for reappraisal of the extent of infection in men. Men attending a sexually transmitted diseases clinic were tested for trichomonas, chlamydia, and gonorrhea. The prevalence of these pathogens was 17%, 19.6%, and 17.7% respectively. In men with NGU, 19.9% were infected with trichomonas. These data have implications for treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
61
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 25 publications
(18 reference statements)
3
61
5
Order By: Relevance
“…The subacute nature of this population, suggesting a substantial proportion of asymptomatic females, is relevant. A number of publications have documented T. vaginalis detection from asymptomatic patients (22,24,25,27). In one of these studies, Schwebke and Hook (25) reported an increased T. vaginalis detection rate in asymptomatic males compared to that in males with symptoms (P ϭ 0.009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subacute nature of this population, suggesting a substantial proportion of asymptomatic females, is relevant. A number of publications have documented T. vaginalis detection from asymptomatic patients (22,24,25,27). In one of these studies, Schwebke and Hook (25) reported an increased T. vaginalis detection rate in asymptomatic males compared to that in males with symptoms (P ϭ 0.009).…”
Section: Discussionmentioning
confidence: 99%
“…A number of publications have documented T. vaginalis detection from asymptomatic patients (22,24,25,27). In one of these studies, Schwebke and Hook (25) reported an increased T. vaginalis detection rate in asymptomatic males compared to that in males with symptoms (P ϭ 0.009). The T. vaginalis detection rate (9.3%) exceeded the detection rates of C. trachomatis (5.7%) and N. gonorrhoeae (1.4%) (P values of Ͻ0.0002 for both) in the current assessment of female epidemiology.…”
Section: Discussionmentioning
confidence: 99%
“…Although the overall prevalence of T. vaginalis in women was approximately 10 to 15% less in this subacute care demographic compared to emergent care populations (16,23,24), significant T. vaginalis detection rates in both males and females (Table 2), as well as statistically increased T. vaginalis detection rates over those of C. trachomatis and N. gonorrhoeae provide evidence supporting consistent molecular screening for this agent. Indeed, appreciable T. vaginalis detection rates have been demonstrated in both symptomatic and asymptomatic populations (25,27,28). …”
Section: Discussionmentioning
confidence: 99%
“…A paucity of studies has examined the role of laboratory diagnosis for management of trichomoniasis in men (2,12,25,28). One of these studies (28) utilized DNA amplification technology to demonstrate detection of T. vaginalis in a greater proportion of asymptomatic males (51.4%) than in those with symptoms (23%; P ϭ 0.009).…”
Section: Discussionmentioning
confidence: 99%
“…Several commercially available real-time PCR assays enable this double detection (3). Trichomonas vaginalis is the most prevalent nonviral sexually transmitted disease pathogen in the world, but it remains poorly diagnosed, as are Mollicutes (Ureaplasmas and Mycoplasmas), which are difficult to cultivate (4)(5)(6). The latter bacteria are involved in early pregnancy loss, stillbirth, preterm birth, and neonatal morbidity, as well as male infertility (6-9), although they are also commonly identified in the vaginal flora of 40% to 80% of healthy women, depending on the population (6, 7).…”
mentioning
confidence: 99%